Handbook the global history of work - Hofmeester, Karin, 1964-; Linden, Marcel van der, 1952- (De Gruyter reference., 2018)
"Coffee from East Africa, wine from California, chocolate from the Ivory Coast -- all those every day products are based on labour, often produced under appalling conditions, but always involving the combination of various work processes we are often not aware of. What is the day-to-day reality for workers in various parts of the world, and how was it in the past? How do they work today, and how did they work in the past? These and many other questions comprise the field of the global history of work -- a young discipline that is introduced with this handbook. In 8 thematic chapters, this book discusses these aspects of work in a global and long term perspective, paying attention to several kinds of work. Convict labour, slave and wage labour, labour migration, and workers of the textile industry, but also workers' organisation, strikes, and motivations for work are part of this first handbook of global labour history, written by the most renowned scholars of the profession"--